New concepts in EBV-associated B, T, and NK cell lymphoproliferative disorders - Quintanilla-Martinez, L (2023)
EBV-associated lymphoproliferative disorders (LPD) include conditions of B, T, and NK cell derivation with a wide clinicopathological spectrum ranging from indolent, self-limiting, and localized conditions to highly aggressive lymphomas. Since the 2016 World Health Organization (WHO) lymphoma classification, progress has been made in understanding the biology of the EBV-associated LPDs. The diagnostic criteria of EBV+ mucocutaneous ulcer and lymphomatoid granulomatosis have been refined, and a new category of EBV-positive polymorphic B cell LPD was introduced to encompass the full spectrum of EBV-driven B cell disorders. The differential diagnosis of these conditions is challenging. This report will present criteria to assist the pathologist in diagnosis. Within the group of EBV-associated T and NK cell lymphomas, a new provisional entity is recognized, namely, primary nodal EBV+ T or NK cell lymphoma. The EBV + T and NK cell LPDs in children have undergone major revisions. In contrast to the 2016 WHO classification, now four major distinct groups are recognized: hydroa vacciniforme (HV) LPD, severe mosquito bite allergy, chronic active EBV (CAEBV) disease, and systemic EBV-positive T cell lymphoma of childhood. Two forms of HV LPD are recognized: the classic and the systemic forms with different epidemiology, clinical presentation, and prognosis. The subclassification of PTLD, not all of which are EBV-positive, remains unaltered from the 2016 WHO classification. This review article summarizes the conclusions and the recommendations of the Clinical Advisory Committee (CAC), which are summarized in the International Consensus Classification of Mature Lymphoid Neoplasms. © 2022, The Author(s).